Performance Measurement Model for the Consumer Industry Listed on Indonesia Stock Exchange: DEA and SFA Approaches - Prabowo, T. Handono Eko; Cabanda, Emilyn (UI Scholars Hub, 2010)
This research attempts to provide performance measurement model for the consumer industry listed on Indonesia Stock Exchange (IDX) by using the data envelopment analysis (DEA) and the stochastic frontier analysis (SFA). There were 36 panel irms analyzed over the period of 2000-2005 or 216 pooled observations. The output variable was total sales and input variables were labor, inventory, ixed assets and capital. Z-variables are age of the irm, size of the irm, market share and time period. Empirical indings reveal that the average technical eficiency (mean TE) for consumer industry was 0.6630. The study indicates the existence of output slacks (output deicits) and input slacks (input wastages) in the consumer industry's operation. The study also shows that the joint effect of four z-variables on the technical ineficiencies of the consumer industry was signiicant although the individual effects of one or more variables might not be statistically signiicant.